Modeling of factors influencing exploration of medical career choices - Rizma Adlia Syakurah; Yayi Suryo Prabandari; Widyandana Widyandana; Taufan Bramantoro (International Journal of Public Health Science (IJPHS), 2021)
Majority of medical students choose clinical specialties as their career choice, compared to other medical fields. This study aimed to finding an effective model of career exploration behaviour in medical students to construct effective career interventions. This study obtained 1030 students of medical faculties in Indonesia. All data used an online survey questionnaire that was collected starting from October 12th-25th 2015. Data analysis used Partial Least Square-Path Modelling using R statistical software to create a model in order to find correlation and pathway among each variable. The result showed both direct and indirect correlation towards the variables studied. Personal accomplishment had a stronger influence on self-efficacy (β=0.317, p<0.001). This study concluded that verbal persuasion and self-efficacy correlate directly to career exploration. All variables are related to career exploration in medical students. Educators and policymakers are able to construct intervention in this area to encourage medical students to start exploring career options early.